The identity of jewel bugs described by Shonen Matsumura from Taiwan (Hemiptera: Heteroptera: Scutelleridae) - Tsai, Jing-Fu; Rédei, Dávid (Zootaxa, 2009)
Shonen Matsumura (1872–1960) Japanese entomologist described four species of jewel bugs (Hemiptera: Heteroptera: Scutelleridae) from Taiwan in 1913. One of them has already been recognized as synonym whilst the identity of three species remained unknown so far. Based on the type material deposited at Hokkaido University, Sapporo, Japan, Matsumura’s species are documented and their identities are clarified. The following new synonymies are proposed: Chrysocoris (Fitha) fascialis (A. White, 1842) = Lamprocoris giranensis Matsumura, 1913, syn. n.; Lamprocoris (Lamprocoris) lateralis (Guérin-Méneville, 1838) = Chrysophara formosana Matsumura, 1913, syn. n.; Poecilocoris druraei (Linnaeus, 1771) = Poecilocoris watanabei Matsumura, 1913, syn. n. Lectotype is designated for Chrysophara formosana. Lamprocoris lateralis is recorded for the first time from Laos and Vietnam.